The dimensions of e-recruitment affect final year students’ perception at Universiti Teknologi MARA (UiTM), Melaka City Campus. - Jaafar, Noor Fadillah; Ishak, Sharmine (2012)
The study had be carried out to identify the dimensions of e-recruitment that affect the final year students’ perception at Universiti Teknologi MARA (UiTM), Melaka City Campus. The main objectives of this research were to examine whether internet familiarity among students affect their perception on e-recruitment, to analyze whether user friendliness influences the students’ perception on e-recruitment, to examine the relationship between publicity and students’ perception on e-recruitment, to identify whether student’s attitudes affect their perception on e-recruitment and also to identify the most influential dimensions of e-recruitment among students’ perception at Universiti Teknologi MARA (UiTM), Melaka City Campus. The sampling size taken from the University were 200 students. The sampling technique used was convenience sampling. The findings indicate user friendliness, internet familiarity, publicity and students’ attitudes become dimensions that affect the students’ perception on e-recruitment and the major factor that influence students’ perception was publicity. This research provided significant information to the students, as a future reference for other studies, also to the UiTM Melaka City Campus administrators and the Faculty.